Conserved and variable heat stress responses of the Heat Shock Factor transcription factor family in maize and Setaria viridis. (27th April 2023) - Myers, Zachary A.; Wootan, Clair M.; Liang, Zhikai; Zhou, Peng; Engelhorn, Julia; Hartwig, Thomas; Nathan, Springer M.
Abstract: The Heat Shock Factor (HSF) transcription factor family is a central and required component of plant heat stress responses and acquired thermotolerance. The HSF family has dramatically expanded in plant lineages, often including a repertoire of 20 or more genes. Here we assess and compare the composition, heat responsiveness, and chromatin profiles of the HSF families in maize and Setaria viridis ( Setaria ), two model C4 panicoid grasses. Both species encode a similar number of HSFs, and examples of both conserved and variable expression responses to a heat stress event were observed between the two species. Chromatin accessibility and genome‐wide DNA‐binding profiles were generated to assess the chromatin of HSF family members with distinct responses to heat stress. We observed significant variability for both chromatin accessibility and promoter occupancy within similarly regulated sets of HSFs between Setaria and maize, as well as between syntenic pairs of maize HSFs retained following its most recent genome duplication event. Additionally, we observed the widespread presence of TF binding at HSF promoters in control conditions, even at HSFs that are only expressed in response to heat stress. TF‐binding peaks were typically near putative HSF‐binding sites in HSFs upregulated in response to heat stress, but not in stable or not expressed HSFs. These observations collectively support a complex scenario of expansion and subfunctionalization within this transcription factor family and suggest that within‐family HSF transcriptional regulation is a conserved, defining feature of the family.